A fluorescent probe for the Fe3+ ion pool in endoplasmic reticulum in liver cells. (July 2016) - Lee, Min Hee; Lee, Hoyeon; Chang, Min Jung; Kim, Hyeong Seok; Kang, Chulhun; Kim, Jong Seung
Abstract: We have presented rhodamine-derived Schiff base probes (1 –6 ) selective of the Fe 3+ ion in biological systems. In the presence of Fe 3+ ions, the probes display new absorption and emission bands at 526 nm and 551 nm, respectively. Confocal microscopic analysis using the HepG2 cell line showed that probes1 –6 provide fluorescence Off–On changes caused by cellular Fe 3+ ions, and demonstrated a largely enhanced fluorescence upon iron overloading of the cells. We also found that the Fe 3+ ion-mediated fluorescence changes of probes1 –6 are mainly localized in the ER (Endoplasmic Reticulum) in HepG2 cells. Among them, probe5 exhibits the highest selectivity for ER localization over the other organelles. Highlights: The probe5 exhibited the selective Fe 3+ -sensing at the organelle level. The probe5 is mainly localized in the Endoplasmic Reticulum in HepG2 cells. It would be very useful for the imaging of Fe 3+ in the ER of iron-overloaded cells.